The impact of employee interactions towards customer satisfaction in cruise services - Anggara, Harleyandri; Supardi; Razak, Anis Abd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to measure the relationship between emotions, role perceptions, perceived control and customer categories towards customer satisfaction. Emotions, role perceptions, perceived control and customer categories are representing the elements of customer interaction which play its own role towards the customer satisfaction based on the situation and type of service based. This study is focusing on the cruise services where both customer interactions and customer satisfaction is important. Data were collected from 150 respondents who voluntarily participated in the survey exercises. Questionnaire were distributed to all tourist who come to Indonesia through cruise services. The results indicate that only two factors are important towards customer satisfaction in relation to the customer satisfaction related to cruise services. Emotions and perceived control are positively significant towards the customer satisfaction. The findings provide a good indicator for the service-based operators to look into those two factors in order to serve customer better. This study is very unique as customer interactions in cruise services is limited within the limited scope. Employee need to be ready and well trained in facing all type of customers. Customer for cruise services coming from various background with a various purposes and intentions. Therefore, meeting the customer needs and wants over a couple of days may give tough challenge should it was not address from the beginning.